2022
DOI: 10.30773/pi.2021.0328
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Korea-Polyenvironmental Risk Score for Psychosis

Abstract: Objective Comprehensive understanding of polyenvironmental risk factors for the development of psychosis is important. Based on a review of related evidence, we developed the Korea Polyenvironmental Risk Score (K-PERS) for psychosis. We investigated whether the K-PERS can differentiate patients with schizophrenia spectrum disorders (SSDs) from healthy controls (HCs). Methods We reviewed existing tools for measuring polyenvironmental risk factors for psychosis, including the Maudsley Environmental Risk Score (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Better representation of interactions between risk factors in a multivariable approach ( e.g ., combining information on momentary stress with trauma history and cortisol levels) is essential for future research, particularly when considering multiple measures of stress, which will be highly correlated. Preliminary work has been encouraging [ 290 ], for example using polyenvironmental risk scores [ 285 , 286 , 291 ] but large, generalisable samples are needed to develop and validate these tools. External validation studies, where independent datasets are used to replicate model performance, are rare in psychiatry [ 288 ] but are needed in order to provide evidence that precision psychiatry tools can perform well in multiple settings and are viable for use in real-world clinical care [ 292 ].…”
Section: Discussionmentioning
confidence: 99%
“…Better representation of interactions between risk factors in a multivariable approach ( e.g ., combining information on momentary stress with trauma history and cortisol levels) is essential for future research, particularly when considering multiple measures of stress, which will be highly correlated. Preliminary work has been encouraging [ 290 ], for example using polyenvironmental risk scores [ 285 , 286 , 291 ] but large, generalisable samples are needed to develop and validate these tools. External validation studies, where independent datasets are used to replicate model performance, are rare in psychiatry [ 288 ] but are needed in order to provide evidence that precision psychiatry tools can perform well in multiple settings and are viable for use in real-world clinical care [ 292 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed that the combination of the specific levels for the four exposures maximizes the differences in obesity risk between girls and boys. Previous studies have already suggested that better prediction of an outcome can be obtained from the aggregation of multiple environmental factors into risk scores [ 49 , 50 ] or the use of mixture models [ 51 ]. In line with this, we used causal inference for classifying the individuals in two environments (E0 and E1) based on the combination of the four exposures.…”
Section: Discussionmentioning
confidence: 99%